Ablation of Myocardial Tissue With Nanosecond Pulsed Electric Fields - Xie, Fei (PLoS One, 2015)
BACKGROUND: Ablation of cardiac tissue is an essential tool for the treatment of arrhythmias, particularly of atrial fibrillation, atrial flutter, and ventricular tachycardia. Current ablation technologies suffer from substantial recurrence rates, thermal side effects, and long procedure times. We demonstrate that ablation with nanosecond pulsed electric fields (nsPEFs) can potentially overcome these limitations. METHODS: We used optical mapping to monitor electrical activity in Langendorff-perfused New Zealand rabbit hearts (n = 12). We repeatedly inserted two shock electrodes, spaced 2–4 mm apart, into the ventricles (through the entire wall) and applied nanosecond pulsed electric fields (nsPEF) (5–20 kV/cm, 350 ns duration, at varying pulse numbers and frequencies) to create linear lesions of 12–18 mm length. Hearts were stained either with tetrazolium chloride (TTC) or propidium iodide (PI) to determine the extent of ablation. Some stained lesions were sectioned to obtain the three-dimensional geometry of the ablated volume. RESULTS: In all animals (12/12), we were able to create nonconducting lesions with less than 2 seconds of nsPEF application per site and minimal heating (< 0.2°C) of the tissue. The geometry of the ablated volume was smoother and more uniform throughout the wall than typical for RF ablation. The width of the lesions could be controlled up to 6 mm via the electrode spacing and the shock parameters. CONCLUSIONS: Ablation with nsPEFs is a promising alternative to radiofrequency (RF) ablation of AF. It may dramatically reduce procedure times and produce more consistent lesion thickness than RF ablation.